PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, PROFITABILITAS, RISIKO BISNIS, DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia tahun 2011-2013) (Students' Journal of Accounting and Banking, 2015)
The purpose of this research is to analyze the effect of size of companies, the liquidity, profitability, business risk and capital structure of assets structure in the manufacturing companies listed on the Indonesia stock exchange period 2011-2013. A kind of data used in this research is of secondary data , this data obtained from icmd ( the indonesian capital market directory ) 2011-2013 .The method used is purposive sampling is a method of the sample collection by means of certain kriteria-kriteria set for 3 years so that the number of data as many as 198 company .A method of data analysis using double linear regression. The results of research shows that the size of company business and risks have the influence of a positive and significant impact on capital structure in partial , variable profitability and liquidity have negative influence to significant and capital structure in partial variable while the structure of the assets have a positive influence and no significant impact on capital structure in partial.Keywords: Capital Structure, The Size of Company, Liquidity, Profitability, The Risk of Business and The Structure of Assets